Community acceptance of the implementation of Movement Control Order (MCO) in Kota Kinabalu City during the Covid-19 pandemic - Nor-Ina Kanyo; Ahmad Tarmizi Abdul Rahman; Mohd Norazmi Nordin; Datu Razali Datu Eranza; Jeannet Stephen; Normah Abdul Latip; Jashmaira binti Kipli (Seybold Publications, 2022)
This paper is related to the implementation of the Movement Control Order (MCO) in the city of Kota Kinabalu, Sabah. The MCO was a preventive measure implemented by the Federal government of Malaysia against the spread of COVID-19 disease which came into force on 18 March 2020. However, the MCO hads several levels and is implemented according to each state’s operating procedures. Among the prohibitions involving the implementation of the MCO were the ban on movement and assembly throughout the country, travel restrictions within and outside the country, the closure of educational institutes, the closure of government and private premises, especially those that were not essential services or the necessary services sector. The implementation of MCO occurred not only in Sabah but also globally. MCOs which were too long and protracted caused the global community to experience problems. Therefore, this study wants to see how communities in Kota Kinabalu accepted the MCO and whether they were also affected by the MCO. The research method used in this study was a mix-method that included reference to several previous studies, newspaper clippings as well as, media reports and distribution of questionnaires. The questionnaire was randomly distributed to the community around the city of Kota Kinabalu. The findings of the study show that the acceptance of the Kota Kinabalu community regarding MCO was at a good level but some were less satisfied. This is because the implementation of MCO was too long and had disrupted the economic and social activities of the population. In addition, public opinion throughout the MCO was also affected.